The Warped Heliospheric Current Sheet. Issue 12 (17th December 2019) - Peng, Jun; Liu, Yong C.‐M.; Huang, Jia; Klecker, Berndt; Wang, Chi
Abstract: The global shape of the intersection of the heliospheric current sheet (HCS) with the heliospheric equatorial plane is usually considered to be an Archimedean spiral, however, so far this has not been measured directly. We used multi‐spacecraft measurements to determine its global shape. The time‐shifted measured locations are fitted with Archimedean spirals. In most cases, the locations are fitted very well with Archimedean spirals, in addition to the direction of HCS determined by the Minimum Variation Analysis. However, there is one case in which the direction of the HCS does not fit well with the Archimedean spiral and therefore we fit it with a sinusoidal function in addition to an Archimedean spiral. The result showed that in some cases, the HCS is better described with an Archimedean spiral, superposed by small‐scale ripples. Key Points: Multi‐spacecraft are used to measure the shape of HCSs The global shape of HCS is proved to be a Parker Spiral Small scale perturbations around some HCS are related to speed evolution